Multimodality imaging approach to left ventricular dysfunction in diabetes: an expert consensus document from the European Association of Cardiovascular Imaging. (5th November 2021) - Marwick, Thomas H; Gimelli, Alessia; Plein, Sven; Bax, Jeroen J; Charron, Phillippe; Delgado, Victoria; Donal, Erwan; Lancellotti, Patrizio; Levelt, Eylem; Maurovich-Horvat, Pal; Neubauer, Stefan; Pontone, Gianluca; et al.
Abstract: Heart failure (HF) is among the most important and frequent complications of diabetes mellitus (DM). The detection of subclinical dysfunction is a marker of HF risk and presents a potential target for reducing incident HF in DM. Left ventricular (LV) dysfunction secondary to DM is heterogeneous, with phenotypes including predominantly systolic, predominantly diastolic, and mixed dysfunction. Indeed, the pathogenesis of HF in this setting is heterogeneous. Effective management of this problem will require detailed phenotyping of the contributions of fibrosis, microcirculatory disturbance, abnormal metabolism, and sympathetic innervation, among other mechanisms. For this reason, an imaging strategy for the detection of HF risk needs to not only detect subclinical LV dysfunction (LVD) but also characterize its pathogenesis. At present, it is possible to identify individuals with DM at increased risk HF, and there is evidence that cardioprotection may be of benefit. However, there is insufficient justification for HF screening, because we need stronger evidence of the links between the detection of LVD, treatment, and improved outcome. This review discusses the options for screening for LVD, the potential means of identifying the underlying mechanisms, and the pathways to treatment.